2017
DOI: 10.4172/2254-609x.100063
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Mushroom (Agaricus Bisporus) and Fungal (Trametes Gibbosa) Extracts from Mushrooms and Fungi of Egerton Main Campus, Njoro Kenya

Abstract: Introduction: The emergence of drug resistance has caught the attention of scientist due to the risk of going back to the pre-antimicrobial era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
(10 reference statements)
4
11
0
Order By: Relevance
“…Ethyl acetate extract exhibited 15, 7.83, 15.17 and 16.17 at 50 mg/ml and at 100 mg/ml it revealed pronounced inhibitory effects causing 30, 20, 19 and 28.67 mm (IZD) against four test plant pathogenic bacteria, P. syringae, R. solanacearum, X. axonopodis and E. carotovora, respectively. The present results showed resemblances with the reports of earlier workers (Kang et al 2015, Soltanian et al 2016, Waithaka et al 2017 on A. bisporus during their research and exhibited 4 mm IZD against R. solanacearum. Ashok et al (2013) also reported antibacterial activity that showed conformity with the present results, where petroleum ether, chloroform and methanolic extract of mushroom Hygro cybeparvula showed 4 mm inhibition zone against P. syringae.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Ethyl acetate extract exhibited 15, 7.83, 15.17 and 16.17 at 50 mg/ml and at 100 mg/ml it revealed pronounced inhibitory effects causing 30, 20, 19 and 28.67 mm (IZD) against four test plant pathogenic bacteria, P. syringae, R. solanacearum, X. axonopodis and E. carotovora, respectively. The present results showed resemblances with the reports of earlier workers (Kang et al 2015, Soltanian et al 2016, Waithaka et al 2017 on A. bisporus during their research and exhibited 4 mm IZD against R. solanacearum. Ashok et al (2013) also reported antibacterial activity that showed conformity with the present results, where petroleum ether, chloroform and methanolic extract of mushroom Hygro cybeparvula showed 4 mm inhibition zone against P. syringae.…”
Section: Resultssupporting
confidence: 92%
“…In agriculture, bacterial invasions bring about serious reduction in the quality and yield of crops and incur enormous economic losses (Navarro et al 2018). At present the most reliable method to control these bacterial pathogens is the use of chemical/synthetic bactericides (Waithaka et al 2017). But the repeated use of these synthetic compounds causes number of ill effects e.g., health hazards, environmental pollution and antibacterial resistance (Ali and Nejad 2016, Marie et al 2016, Erjavec et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Gram-positive bacteria such as E. coli , K. pneumoniae (ATCC 13883), P. aeruginosa (clinical isolate), and P. aeruginosa (ATTC 27853) were the most resistant to almost all extracts. These results clearly confirm that Gram-positive bacteria are highly susceptible to the extracts and were in agreement with the previous reports [11, 23]. For example, Akyuz and Kirbag [24] concluded that the extracts of Agaricus bisporus and Pleurotus florida were found to have better inhibitory activities against Gram-negative compared to Gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…Trametes species showed activity against both test organisms. Species of this genus possess secondary metabolites that have broad spectrum antibacterial activity (Waithaka et al, 2017).…”
Section: Antibacterial Activity Of Isolated Fungal Endophytes and Extmentioning
confidence: 99%